Integration of a Mindfulness Meditation Lab for University Students - Duke D. Biber (The Ohio State University Libraries, 2020)
Background: Mindfulness meditation can effectively enhance every dimension of holistic wellness and learning, including cognition, attention, self-regulatory resources, and first-year academic success. Aim: This paper discusses the potential impact of a mindfulness meditation room on student wellness, education, experiential learning, and development. Methods: The program curriculum and the structure of the Wolf Wellness Lab at the University of West Georgia emphasizes a holistic approach to higher education curriculum development and student wellness and is based on the National Wellness Institute's six dimensions of wellness. The newly developed mindfulness meditation room is discussed in regard to recent research and valid, practical application as a way to improve student learning and overall wellness. Conclusions: The mindfulness meditation room provides experiential learning and high-impact practices associated with the University of West Georgia educational curriculum. The mindfulness meditation room could promote student learning and overall well-being via personal practice and opportunities to guide other students and faculty through meditation practice.